The Washington, DC Media Corps in the 21st Century : The Source-Correspondent Relationship - Hellmueller, Lea.; SpringerLink (Online service) (New York : Imprint: Palgrave Macmillan, 2014)
The book provides a fresh perspective on the shifting media landscape within Washington DC, re-evaluating journalist-source relationships, the power dynamic within the media corps, and the ways in which technology have changed the description of DC political news - detailing the ways in which media relationships are changing within Washington DC.
Keywords: Science